Leadership in turbulent times - Goodwin, Doris Kears (London Penguin, 2019)
Are leaders born or made? Where does ambition come from? How does adversity affect the growth of leadership? Does the leader make the times or do the times make the leader?
Includes index
Keywords: Leadership; Presidents -- United States -- History; United States -- Politics and government